2022
DOI: 10.1038/s41598-022-12652-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of kidney dysfunction in COVID-19 and the influence of age

Abstract: COVID-19 is strongly influenced by age and comorbidities. Acute kidney injury (AKI) is a frequent finding in COVID-19 patients and seems to be associated to mortality and severity. On the other hand, the role of kidney dysfunction in COVID-19 is still debated. We performed a retrospective study in a cohort of 174 hospitalized COVID-19 patients in Italy from March 3rd to May 21st 2020, to investigate the role of kidney dysfunction on COVID-19 severity and mortality. Moreover, we examined in depth the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Kidney dysfunction is a common consequence of SARS-CoV-2 infection ( 1 , 2 ), having been reported in adults and, to a lesser degree, in children. Kidney consequences of COVID-19 can include a broad spectrum of damages, ranging from acute kidney injury (AKI) with glomerular or tubular injury to mild proteinuria and/or hematuria ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kidney dysfunction is a common consequence of SARS-CoV-2 infection ( 1 , 2 ), having been reported in adults and, to a lesser degree, in children. Kidney consequences of COVID-19 can include a broad spectrum of damages, ranging from acute kidney injury (AKI) with glomerular or tubular injury to mild proteinuria and/or hematuria ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, both the brain-specific and kidney-specific models could predict disease severity. Acute kidney injury is a common occurrence in COVID-19 patients (La Porta et al, 2022), and severe COVID has been linked to accelerated brain aging (Mavrikaki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies demonstrated that chronic inflammation, a salient feature in HD patients, might protect those patients from severe COVID-19-related symptoms, ICU admission, and mortality [ 9 , 16 ]. These discordant results are accepted because of the limitations known in the observational studies and multiple confounders which can affect the patient prognosis like age [ 37 ], associated comorbidities, and selection bias. The present study revealed a better survival rate, less severe hypoxemia indicating hospital or ICU admission in COV-HD than COV patients despite the comparable age, comorbidity, radiological severity criteria.…”
Section: Discussionmentioning
confidence: 99%